The fabulous Zed Watson! - Sylvester, Basil; Sylvester, Kevin (HarperCollins Publishers Ltd, 2021)
"The literary scavenger hunt of a lifetime, starring an endlessly endearing non-binary tween Zed Watson loves a few things: their name (which they chose themself!), their big rambunctious family, and--oh yeah--monsters. When Zed discovered the mystery surrounding an unpublished novel called The Monster's Castle, they were completely hooked. Now Zed is a member of a small but dedicated legion devoted to finding the long-buried text. When a breakthrough discovery leads Zed to the route that they are sure will take them to the treasure, they know it's time for a road trip. And with the help of their shy, flora-loving neighbour, Gabe, and his sister, Sam, a geologist who is driving back to college in Arizona, Zed and company are soon off on a wild adventure following cryptic clues. But it's not all fun and games. Gabe doesn't like Zed's snacks, Sam is a bossy driver with total command of the ancient Impreza's stereo, and Zed is often misgendered. It's a good thing they also encounter kind strangers, potato-themed dance-offs and lots and lots of ice cream along the way. If Zed and Gabe can combine their strengths, survive Sam's wrath and best the greedy historian who's also hot on the book's trail, they just might find the greatest treasure of all. Co-authored by child-parent duo Basil Sylvester and Kevin Sylvester, this is a vibrant and enormous-hearted story about friendship, identity and belonging. It features illustrations by celebrated author and illustrator Kevin Sylvester, and an Own Voices perspective based on Basil's experience."--